A phase I/II study of biweekly capecitabine and irinotecan plus bevacizumab as second-line chemotherapy in patients with metastatic colorectal cancer - Suenaga M; Mizunuma N; Matsusaka S; Shinozaki E; Ozaka M; Ogura M; Chin K; Yamaguchi T (Dove Medical Press, 2015)
Mitsukuni Suenaga,1 Nobuyuki Mizunuma,1 Satoshi Matsusaka,1 Eiji Shinozaki,1 Masato Ozaka,1 Mariko Ogura,1 Keisho Chin,1 Toshiharu Yamaguchi2 1Department of Gastroenterology, 2Department of Gastroenterological Surgery, Cancer Institute Hospital of Japanese Foundation for Cancer Research, Ariake, Koto-ku, Tokyo, Japan Background: Triweekly capecitabine plus irinotecan (XELIRI) is not completely regarded as a valid substitute for fluorouracil, leucovorin, and irinotecan (FOLFIRI) in metastatic colorectal cancer (mCRC) because of the potential for greater toxicity. We conducted a phase I/II study to assess the efficacy and safety of biweekly XELIRI plus bevacizumab (BV) as second-line chemotherapy for mCRC.Methods: Patients with mCRC who had received prior chemotherapy including oxaliplatin and BV and had a UGT1A1 genotype of wild-type or heterozygous for UGT1A1*6 or *28 were eligible for this study. Treatment comprised capecitabine 1,000 mg/m2 twice daily from the evening of day 1 to the morning of day 8, intravenous irinotecan on day 1, and BV 5 mg/kg on day 1 every 2 weeks. The phase I study consisted of two steps (irinotecan 150 and 180 mg/m2), and dose-limiting toxicity was assessed during the first treatment cycle. The primary endpoint of the phase II study was progression-free survival (PFS).  Results: The recommended dose of irinotecan was determined to be 180 mg/m2 in the phase I study. Between November 2010 and August 2013, 44 patients were enrolled in phase II. The patients’ characteristics were as follows (N=44): median age, 60 years (range 32–80); male/female, 21/23; and UGT1A1 wild-type/heterozygous, 29/15. The median PFS was 6.8 months (95% confidence interval, 5.3–8.2 months), and the primary endpoint was met. Median overall survival was 18.3 months. The response rate was 22.7%. There was no significant difference in PFS or overall survival according to UGT1A1 status. Grade 3 or higher adverse events were mainly neutropenia in six patients and diarrhea in five patients. There were no other severe adverse events or treatment-related deaths.Conclusion: In mCRC patients with wild-type or heterozygous UGT1A1*6 or *28 genotype, biweekly XELIRI + BV is effective and feasible as second-line chemotherapy. Biweekly XELIRI + BV is considered a valid substitute for FOLFIRI + BV in mCRC. Keywords: XELIRI, bevacizumab, metastatic colorectal cancer, UGT1A1